2019
DOI: 10.1158/1078-0432.ccr-18-3185
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Open-Label, Multicenter Study of First-in-Class RORγ Agonist LYC-55716 (Cintirorgon): Safety, Tolerability, and Preliminary Evidence of Antitumor Activity

Abstract: Purpose: Transcription factor retinoic acid receptor-related orphan receptor g (RORg) regulates type 17 effector T-cell differentiation and function and is key to immune cell regulation. Synthetic RORg agonists modulate immune cell gene expression to increase effector T-cell activity and decrease immune suppression. A phase 1 study evaluated the safety and tolerability of LYC-55716 (cintirorgon), a first-in-class, oral, small-molecule RORg agonist in adults with relapsed/ refractory metastatic cancer.Patients … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…This highlights the complexity of the immune response in secukinumab and CPI treatments, and the need for additional studies in patients with different cancers and irAEs. Of note, in a Phase I clinical trial, the RORγ agonist cintirorgon (LYC-55716), that promotes Th17 cell expansion, was well tolerated and induced both partial tumor response and stable disease, including in patients with solid tumors that were previously exposed to CPI treatment (NCT02929862) vi [79]. An additional clinical trial has been initiated in non-small cell lung cancer to assess the toxicity profile and tumor response following cintirorgon and pembrolizumab (NCT03396497) vii .…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
“…This highlights the complexity of the immune response in secukinumab and CPI treatments, and the need for additional studies in patients with different cancers and irAEs. Of note, in a Phase I clinical trial, the RORγ agonist cintirorgon (LYC-55716), that promotes Th17 cell expansion, was well tolerated and induced both partial tumor response and stable disease, including in patients with solid tumors that were previously exposed to CPI treatment (NCT02929862) vi [79]. An additional clinical trial has been initiated in non-small cell lung cancer to assess the toxicity profile and tumor response following cintirorgon and pembrolizumab (NCT03396497) vii .…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
“…Circadian pharmacologic studies show that RORγ agonists, which can activate BMAL1 transcription [73], attenuate the expression of PD-1 receptors [33]. The RORγ agonist LYC-55716 has demonstrated initial success in Phase 1 clinical trials as a single agent for locally advanced or metastatic solid tumors of multiple types (clinical trial NCT02929862): good tolerability, safety, and pharmacokinetics were observed, as well as partial responses in 6% patients and disease stabilizations in 34% patients over 12-month follow-up [74]. A similar Phase 1 trial of LYC-55716 used in combination with pembrolizumab for non-small cell lung cancer is underway (NCT03396497).…”
Section: Circadian Clock Genes and Immunotherapiesmentioning
confidence: 99%
“…Pharmacologic manipulation of circadian signaling has the potential to reset rhythms in a circadian misaligned organism, which could facilitate appropriate timing of anti-cancer drug delivery to synchronize with times at which healthy cells would be most resistant to off-target effects. Several promising circadian-targeting compounds have also been developed that in-and-of themselves show strong anti-cancer effects in vitro and in vivo [35,73,74]. Not only are circadian agonists capable of inducing tumor cell death while producing no off-target (healthy cell) effects or toxicities, lethality has been observed in tumors depending upon upregulated signalers such as H-RAS, K-RAS, BRAF, PIK3CA, as well as in p53 null tumor cells [35].…”
Section: Improving Clinical Measurement Of Circadian Disruptionmentioning
confidence: 99%
“…85 Interestingly, the synthetic RORgt agonist cintirorgon (¼ LYC-55716) was deemed safe for use in various types of cancer in a recent phase I clinical trial. 86 Myeloid-derived suppressor cells (MDSC) are known suppressors of the immune systemespecially T cells -(reviewed in ref. 87) and can directly exert various protumor effects (reviewed in ref.…”
Section: Consequences Of Ror (Inverse) Agonism and Rors As Drug Targetsmentioning
confidence: 99%